Crosstalk between the Ketogenic Diet and Epilepsy: From the Perspective of Gut Microbiota - Yuying Fan; Hua Wang; Xueyan Liu; Junmei Zhang; Gang Liu (Mediators of Inflammation)
Given the association between a range of neurological disorders and changes in the gut microbiota, interest in the gut microbiota has recently increased. In particular, the significant involvement of the autoimmune processes in the development of epilepsy, one of the most serious and widespread neurological diseases, has led to a suggested link with the gut microbiome. Because the constitution of the gut microbiome can be influenced by diet, dietary therapy has been shown to have a positive impact on a wide range of conditions via alteration of the gut microbiota. An example of one such diet is the ketogenic diet (KD), which promotes a diet that contains high levels of fat, adequate levels of protein, and low levels of carbohydrate. Due to the near-total elimination of carbohydrates from the individual’s food in this ultra-high-fat diet, ketone bodies become an important source of energy. Although the ketogenic diet has proven successful in the treatment of refractory epilepsy and other illnesses, the underlying mechanisms of its neuroprotective effects have yet to be fully elucidated. Nevertheless, recent studies strongly indicate a role for the gut microbiota in the effective treatment of epilepsy with the ketogenic diet. The latest advances regarding the links between the ketogenic diet, gut microbiota, and epilepsy are reviewed in this article, with a particular focus on the role of the gut microbiota in the treatment outcome.